The structure of the TOG‐like domain of Drosophila melanogaster Mast/Orbit. Issue 7 (22nd July 2013) - De la Mora‐Rey, Teresa; Guenther, Brian D.; Finzel, Barry C.
<x xml:space="preserve">Abstract</x> Mast/Orbit is a nonmotor microtubule‐associated protein (MAP) present in Drosophila melanogaster that reportedly binds microtubules at the plus end and is essential for mitosis. Sequence analysis has shown that the N‐terminal domain (Mast‐M1) resembles TOG domains from the Dis1‐TOG family of proteins and stands as a representative of one of the three subclasses of divergent TOG‐like domains (TOGL1) that includes human CLASP1. The crystal structure of Mast‐M1 has been determined at 2.0 Å resolution and provides the first detailed structural description of any TOG‐like domain. The structure confirms that Mast‐M1 adopts a similar fold to the previously described Dis1‐TOG domains of microtubule‐binding proteins. A comparison with three known TOG‐domain structures from XMAP215/Dis1 family members exposes significant differences between Mast‐M1 and other TOG‐domain structures in key residues at the proposed tubulin‐binding edge.